CD274 promotes cell cycle entry of leukemia-initiating cells through JNK/Cyclin D2 signaling. Issue 1 (December 2016) - Fang, Xia; Chen, Chiqi; Xia, Fangzhen; Yu, Zhuo; Zhang, Yaping; Zhang, Feifei; Gu, Hao; Wan, Jiangbo; Zhang, Xiaocui; Weng, Wei; Zhang, Cheng; Chen, Guo-Qiang; et al.
Abstract Background CD274 (programmed death ligand 1, also known as B7H1) is expressed in both solid tumors and hematologic malignancies and is of critical importance for the escape of tumor cells from immune surveillance by inhibiting T cell function via its receptor, programmed death 1 (PD-1). Increasing evidence indicates that functional monoclonal antibodies of CD274 may potently enhance the antitumor effect in many cancers. However, the role of CD274 in leukemia-initiating cells (LICs) remains largely unknown. Methods We established an MLL-AF9-induced acute myeloid leukemia (AML) model with wild-type (WT) and CD274-null mice to elucidate the role of CD274 in the cell fates of LICs, including self-renewal, differentiation, cell cycle, and apoptosis. RNA sequencing was performed to reveal the potential downstream targets, the results of which were further validated both in vitro and in vivo. Results In silico analysis indicated that CD274 level was inversely correlated with the overall survival of AML patients. In Mac-1+ /c-Kit+ mouse LICs, CD274 was expressed at a much higher level than in the normal hematopoietic stem cells (HSCs). The survival of the mice with CD274-null leukemia cells was dramatically extended during the serial transplantation compared with that of their WT counterparts. CD274 deletion led to a significant decrease in LIC frequency and arrest in the G1 phase of the cell cycle. Interestingly, CD274 is not required for the maintenance of HSC pool as shown in our previous study. Mechanistically, we demonstrated that the levels of both phospho-JNK and Cyclin D2 were strikingly downregulated in CD274-null LICs. The overexpression of Cyclin D2 fully rescued the loss of function of CD274. Moreover, CD274 was directly associated with JNK and enhanced the downstream signaling to increase the Cyclin D2 level, promoting leukemia development. Conclusions The surface immune molecule CD274 plays a critical role in the proliferation of LICs. The CD274/JNK/Cyclin D2 pathway promotes the cell cycle entry of LICs, which may serve as a novel therapeutic target for the treatment of leukemia.